Citra Pembelajaran Sejarah dalam Persepsi Siswa - B. Fitri Rahmawati; Muhammad Shulhan Hadi; Hubaidiyah Hubaidiyah (Universitas Hamzanwadi, 2022)
The purpose of this research is to describe students' perceptions of history learning. The method used in this research is descriptive qualitative. This research was conducted at the Madrasah Aliyah Nurussalam Tetebatu, East Lombok for students of class XI IIS. Data collection techniques using interviews, observation, open questionnaires and documentation. Data were analyzed using data analysis techniques by Miles and Huberman, namely data reduction, data display and data verification. The results of this study show a picture of the image of learning history based on student perceptions which can be seen from the subject matter, learning media, learning resources, learning methods and learning evaluation. According to students, historical material is quite easy to understand, but there are obstacles such as difficulty understanding foreign terms, boring learning, class hours at the end so students fall asleep. Teachers have also used learning media such as textbooks, blackboards and markers. Such media is considered boring and not varied. Students expect learning outside the classroom that utilizes the environment as a learning medium. Likewise with learning resources, which are still less varied. Teachers are more dominant in using books as learning resources, while environmental media which is the hope of students, have not been used optimally. While the learning methods most widely used by teachers are lecture methods, discussion methods and question and answer methods. Meanwhile, to evaluate history lessons, the teacher uses the method used by the teacher in the form of assignments, daily tests and end-of-semester exams.